Avaliação de programa de psicoeducação em pacientes com transtorno afetivo bipolar - Silvia Mendonca da Matta (2012)
Bipolar disorder (BD) is a chronic disease that causes serious harm to patient and society. Although his first choice of treatment is pharmacotherapy, adjuvant non-pharmacological treatments are useful in maximizing clinical efficacy. Psychoeducation is a treatment modality that provides the patient and / or family guidance on a certain condition in order to improve their prognosis, aiming to increase adherence to drug treatment and relapse prevention. There are evidences in literature that treatment, besides being low cost, is efficient in the handling and prevention of chronification of the disease. The objective of this research was to investigate the impact of a psychoeducational program in relation to clinical variables in patients with BD followed at the Bipolar Disorder Clinic of HC-UFMG. A systematic psychoeducational program was adapted from the Barcelona program for patients affected by BD, after the literature review. The program was divided into six meetings on a weekly basis. Forty-eight patients treated at the Clinic of Bipolar Disorder HC-UFMG were selected and assigned into two groups, experimental or control (27 in the experimental group and 21 in control group). The experimental group received the psychoeducation and the conventional treatment (pharmacological). The control group received only conventional treatment. Patients were followed monthly for five months in order to evaluate the clinical variables of pharmacological treatment, psychiatric hospitalizations, mood episodes and suicide attempts. Of the 48 individuals who initially consented to participate in the research, 44 (91.6% of the initial sample) were followed monthly, so that most patients in the experimental group (66.7%) attended most or all sessions of psychoeducation (4-6 sessions). Over the five months after the monitoring program, the scores of depressive symptoms in the group who attended four or more sessions remained lower than the control group, without statistical significance, however, between the groups during the follow-up. Psychoeducation has shown benefits in reducing rates of noncompliance (p < 0.01), as well as the number of psychiatric hospitalizations (p < 0.01) and suicide attempts (p = 0.02). Since psychoeducation, finally, is a low-cost intervention and the benefits are more consistent, it is of great importance in the implementation of investment programs of psychoeducation in public health, offering not only a space for the community to be assisted, but also for training of professionals capable of conducting this kind of treatment in other public services in the area of mental health